1999
DOI: 10.1080/088800199277029
|View full text |Cite
|
Sign up to set email alerts
|

METASTATIC OVARIAN NEUROBLASTOMA: A Case Report

Abstract: Ovarian metastasis of childhood tumors is rare despite their aggressive nature. The childhood tumor that spreads to the ovary most frequently is the neuroblastoma. The clinical features and frequent bilaterality of ovarian metastatic tumors are helpful diagnostic features in many cases, but when the ovarian tumor is the presenting manifestation of the disease, differentiation from various primary ovarian tumors may be difficult. In this paper, a rare case of metastatic ovarian neuroblastoma is reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…Data on histological analysis were available for patients who had ovarian tissue cryopreservation for medulloblastoma and neuroblastoma and suggested no ovarian involvement (Poirot et al, 2007;Azem et al, 2010). Nevertheless, case reports and autopsy data have indicated that ovarian involvement in neuroblastoma does occur (Himelstein-Braw et al, 1977;Meyer et al, 1979;Sty et al, 1980;Young et al, 1993;Somjee et al, 1999;McCarville et al, 2001;Miyauchi et al, 2004).…”
Section: Other Tumoursmentioning
confidence: 99%
“…Data on histological analysis were available for patients who had ovarian tissue cryopreservation for medulloblastoma and neuroblastoma and suggested no ovarian involvement (Poirot et al, 2007;Azem et al, 2010). Nevertheless, case reports and autopsy data have indicated that ovarian involvement in neuroblastoma does occur (Himelstein-Braw et al, 1977;Meyer et al, 1979;Sty et al, 1980;Young et al, 1993;Somjee et al, 1999;McCarville et al, 2001;Miyauchi et al, 2004).…”
Section: Other Tumoursmentioning
confidence: 99%
“…Ovarian involvement appeared to be an autopsy finding in the majority of cases, as roughly one-third of neuroblastoma cases were reported to have ovarian tumour deposits histologically 8. In 2001, McCarville et al described a neuroblastoma case in whom the ovarian metastasis were diagnosed concomitantly, and in 2009, Somjee et al reported a 15-year-old girl who also had metastatic ovarian involvement 9 10…”
Section: Discussionmentioning
confidence: 99%
“…Although several studies have described the presence of metastases in NB, none have systematically sought ovarian metastases or explored the involvement of the ovaries as the study aim. Very few case reports of metastatic ovarian involvement in patients with NB have been described in the literature, yet NB is the childhood tumor that most frequently metastases to the ovary . Moreover, more than 60% of childhood metastatic NBs have circulating tumor cells at the time of diagnosis …”
Section: Discussionmentioning
confidence: 99%
“…The possible presence of tumor cells in the ovarian tissue collected from females with NB should be borne in mind for several reasons. In all the previously published studies, only histological analyses were performed, on only one to three randomly selected ovarian fragment sections, and this is not a highly sensitive technique for MRD detection …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation